ANALISIS PERAN ORANG TUA DALAM PEMBELAJARAN DARING SISWA KELAS I SEKOLAH DASAR DI KAMPUNG MAKASAR JAKARTA TIMUR - Putri Nurul Mutiarahuda; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
The role of parents in accompanying and educating children is not limited to being parents. These main roles and responsibilities can be realized by guiding children to learn continuously at home in accordance with the curriculum that children learn at school. Online learning aims to provide high-quality learning services through an open network (online) to reach a wider audience. The primary school level, especially Grade I, requires more assistance from parents when learning online, because the level of understanding, ability and independence of Grade I elementary school children is still very low. This study aims to analyze the role of parents in online learning and to find out what are the positive and negative impacts of online learning. This study is a qualitative research using descriptive approach and researchers conducted sampling using simple random sampling technique (simple random sample). The results of this study indicate that the application of online learning is not fully in accordance with the objectives for Grade I Elementary School students, especially in Kampung Makasar housing, East Jakarta. Mentoring and activeness of parents in accompanying children will determine the extent to which learning activities at home will be useful and meaningful. The negative impact of online learning is that children become addicted to gadgets because learning requires using gadgets, as well as the existence of more expenses to fill the internet quota and even have to buy mobile phones for their children to smooth online learning. The positive impact of this online learning makes Grade I elementary school children more coordinated by parents and online learning also relies on technology in the process, so that parents and children can add knowledge and insight through learning media applications that are used to add material to the learning process runs smoothly.